Wave modelling in coastal and inner seas - Cavaleri, L.; Abdalla, S.; Benetazzo, A.; Bertotti, L.; Bidlot, J.-R.; Breivik, Ø.; Carniel, S.; Jensen, R.E.; Portilla-Yandun, J.; Rogers, W.E.; Roland, A.; Sanchez-Arcilla, A.; et al. (Progress in oceanography, 2018)
•A summary of the present state of the art in enclosed sea wave modelling.•Many examples of present modelling capability and limitations.•A deep discussion and analysis of wave-current interactions and modelling.•A discussion of the present state of the art in wave modelling.•A look and a prospect for the corresponding possible future developments. In the long term development of the research on wind waves and their modelling, in particular of the inner and coastal seas, the present situation is framed with a short look at the past, a critical analysis of the present capabilities and a foresight of where the field is likely to go. After a short introduction, Chapter 2 deals with the basic processes at work and their modelling aspects. Chapter 3 highlights the interaction with wind and currents. Chapter 4 stresses the need for a more complete, spectral, approach in data assimilation. Chapter 5 summarizes the situation with a discussion on the present status in wave modelling and a look at what we can expect in the future.